2019
DOI: 10.1101/609958
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Biofluid modeling of the coupled eye-brain system and insights into simulated microgravity conditions

Abstract: This work aims at investigating the interactions between the flow of fluids in the eyes and the brain and their potential implications in the development of visual impairment in astronauts, a condition also known as spaceflight associated neuro-ocular syndrome (SANS). To this end, we propose a reduced (0-dimensional) mathematical model of fluid flow in the eyes and brain, which is embedded into a simplified whole-body circulation model. In particular, the model accounts for: (i) the flows of blood and aqueous … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“… 7 Aside from in vivo measurements, a mathematical model of fluid flow in the eyes and brain embedded into a simplified whole-body circulation model predicted raised ICP and IOP in microgravity. 19 This model predicted decreased ocular blood flow to the choroid and ciliary body whereas retinal circulation was found to be less susceptible to microgravity induced changes.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“… 7 Aside from in vivo measurements, a mathematical model of fluid flow in the eyes and brain embedded into a simplified whole-body circulation model predicted raised ICP and IOP in microgravity. 19 This model predicted decreased ocular blood flow to the choroid and ciliary body whereas retinal circulation was found to be less susceptible to microgravity induced changes.…”
Section: Resultsmentioning
confidence: 90%
“…Aside from technology that could be used inflight, there are various reports of novel approaches to increase our understanding of SANS. Salerni et al 19 reported a mathematical model of fluid flow in the eyes and brain which predicted increased ICP and IOP in microgravity, as well as decreased ocular blood flow in the choroid and ciliary body. As noted above, the lymphatic system has been proposed to play a role in contributing to SANS, and Rasmussen et al 32 described a technique that could be used to further our understanding of this.…”
Section: Resultsmentioning
confidence: 99%
“…To date, only preliminary mathematical models linking ocular dynamics with the cardiovascular system and the dynamics in other organs, such as the kidney and brain, are available. 9 Several mathematical models studying systems separately have been previously developed; [6][7][8] however, the coupling of the different vascular and structural components involved introduces multiple challenges. Specifically, the coupling involves the following multiscale and multiphysics components: fluid flows (e.g.…”
Section: Introductionmentioning
confidence: 99%